The Role of Citizenship Education Teachers in Shaping the Character of Fourth-Grade Elementary School Students - Wili Ariska; Aisyah Putri Dea Palupi (Journal on Education, 2024)
This study seeks to investigate the influence of Civic Education teachers on student character development and the specific measures used in this regard at SD Negeri 38 Kota Pagar Alam. This study tries to generate a comprehensive and accurate depiction of this phenomenon by employing a qualitative methodology. Interviews, observations, and documentation gathered data. The findings indicate that teachers have multiple important functions in forming student character during Civic Education sessions, which can be summed by the acronym MODEVIK: motivator, dynamizer, evaluator, inspirator, and example. Teachers serve as motivators by employing personalized ways and providing encouragement to enhance the learning spirit of less enthusiastic students. Meanwhile, teachers operate as dynamizers by creating a favorable learning atmosphere through activities such as including prayer before learning, organizing ice-breaking sessions, and engaging in song sessions with pupils